'You'll find lots of help here' unpacking the function of an online Rheumatoid Arthritis (RA) forum. (January 2016) - Angouri, Jo; Sanderson, Tessa
Abstract: The paper reports on the analysis of online postings from a Rheumatoid Arthritis asynchronous forum. Despite the rapid increase of internet users, the role of health related online communities is still underexplored. In this paper we draw on sociolinguistics and medical sociology research in order to problematize the online community notion and to unpack the functions of one forum through the analysis of data from newly diagnosed users. The analysis of the threads shows that the users orient to a set of roles which include both task and rapport oriented functions. We close the paper by showing how the members contribute to the construction of a collective identity. Finally we return to the theoretical considerations raised in our paper and identify areas for further research. Highlights: We report on the functions of an online Rheumatoid Arthritis forum. We draw on sociolinguistic and medical sociology research and discuss the community notion. We show how thematic analysis can complement the micro analysis of interaction. We foreground areas for further research in online health fora.